Wasting in Chronic Kidney Disease – a Complex Issue. Issue 2 (1st July 2018) - Slee, Adrian D; Reid, Joanne
Abstract: Chronic kidney disease (CKD) has become a global health burden and is associated with increased morbidity and mortality. In particular, wasting is highly prevalent in later stages of the illness with muscle loss being a common problem. The aetiology and progression of this wasting is complex and multiple states have been identified linked to wasting in CKD. These include: 'malnutrition', 'disease‐related malnutrition', 'protein‐energy wasting', 'cachexia', 'sarcopenia', 'frailty' and 'muscle wasting'. The purpose of this paper is to review these terms in the context of CKD. Common features include weight loss, loss of muscle mass and muscle function principally driven by CKD disease specific factors and inflammatory mediators. Disease‐related malnutrition would appear to be a more appropriate term for CKD than malnutrition as it take in to consideration disease specific factors such as inflammation for example. Frailty is commonly associated with age‐related decline in physiological function. Development of novel screening tools measuring across multiple domains of nutritional status, muscle and physical function may be useful in CKD. Research into potential treatments are currently underway with focus on multi‐modal therapies including nutrition, resistance training and anabolic drugs such as myostatin blockade and selective androgen receptor modulators. A better understanding of different states and terms may help guide assessment and treatment opportunities for patients.